Prioritization of barriers to halal certification adoption for food SME: a study using Fuzzy Analytic Hierarchy Process - Utama, Dana Marsetiya; Ramadhani, Taufik Akbar; Dewi, Shanty Kusuma (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Halal certification plays a crucial role in boosting Muslim consumer confidence and expanding both domestic and international market opportunities. However, small and medium enterprises (SMEs) often encounter significant challenges in obtaining this certification. This study explores the barriers faced by food SMEs in Malang Regency, Indonesia, in adopting halal certification and offers recommendations to address them. Using the fuzzy analytical hierarchy process (AHP) method, the study evaluates and ranks 20 identified barriers. The results show that the main obstacles are limited capital for certification registration, complicated registration process, and weak enforcement and compliance with the halal logo. This study emphasizes the importance of adopting halal certification for food SMEs to access the global market. The AHP approach proved effective in assessing the barriers hierarchically and systematically. Recommendations are provided to improve food SMEs' understanding of halal certification requirements to enhance product competitiveness in the international market.